Graphene-based transparent conductive electrodes for GaN-based light emitting diodes: Challenges and countermeasures. (March 2015) - Wang, Liancheng; Liu, Wei; Zhang, Yiyun; Zhang, Zi-Hui; Tiam Tan, Swee; Yi, Xiaoyan; Wang, Guohong; Sun, Xiaowei; Zhu, Hongwei; Volkan Demir, Hilmi
Abstract: Graphene, with attractive electrical, optical, mechanical and thermal properties, is considered to be an ideal candidate for transparent conductive electrodes (TCEs) in many optoelectronic devices, including III-nitride based devices. However, high contact resistivity ( ρ c ) between graphene and GaN (especially p-GaN) has become a major challenge for graphene TCEs utilization in GaN-based light-emitting diodes (LEDs). Here, we analyzed the graphene/GaN contact junction in detail and reviewed the current research progress for reducing ρ c in graphene TCEs on GaN LEDs, including interface engineering, chemical doping and tunnel junction design. We also analyzed the current diffusion length for a single layer graphene (SLG) and multiple layer graphene (MLG) TCEs. Finally, to improve the fabrication process compatibility and simplicity with paramount reproduction, a method of directly growing graphene films on GaN by chemical vapor deposition (CVD) is proposed. We also give a short analysis on the reliability of graphene TCEs for GaN-based LEDs. It is believed that this is the ultimate solution for graphene TCEs application for GaN-based LEDs and others in general for other opto- and electrical devices. Graphical abstract: We review the graphene transparent conductive electrodes for GaN-based light emitting diodes and propose here the tunneling junction combined local graphene growth approach. Highlights: Overview of current status for graphene transparent conductive electrodes. GaN/graphene contact analysis. Review of graphene transparent conductive electrodes for GaN-based LEDs by interface engineering and chemical doping. Two approaches proposed: tunnel junction (TJ) and local graphene growth on GaN.